Adaptation, Hauntology, and the Video Essay: Kubrick’s Shining - An Adaptive Poem - Marcus Nicholls (Screenworks)
This video essay and accompanying research statement discuss ideas of hauntology in relation to adaptation, both in written analysis and in creative practice research. The video essay combines a visual remix of imagery from Kubrick’s adaptation of The Shining with a written poem which itself adapts the film in an ekphrastic form. The two combine to produce a ‘poetic’ video essay which uses formal and conceptual layerings and superimpositions to embody ideas of palimpsestuous hauntedness. The accompanying research statement outlines these ideas in a more traditional form. Broader discussions of the ways in which the theory and practice of adaptation relate to creative practice research, the video essay form, and theories of hauntology, are grounded by analysing a relevant video essay by Catherine Grant, ‘The Haunting of the Headless Woman.’ The exegesis of this work provides a framework for critically viewing ‘The Shining: An Adaptive Poem.’ Between the layers of the statement and the video essay, ideas around adaptation’s hauntological nature are set in productive debate, blurring theory and practice through spectral metaphors.